Self-employment in Germany: The trend has been increasing for some time - Michael Fritsch; Alexander Kritikos; Alina Rusakova (DIW Economic Bulletin, 2012)
Entrepreneurial self-employment in Germany has undergone a strong upturn in the last 20 years. The number of self-employed people rose by 40 percent between 1991 and 2009. The reasons for this development are the catch-up processes in eastern Germany, structural change towards the service sector, and a strong willingness among the highly skilled, the unmarried and among foreigners to enter self-employment. Furthermore, the percentage of women becoming involved in start-ups increased substantially during the monitoring period. The decision to take up self-employment generally pays off: after three years, 38 percent of all entrepreneurs still being active in the market had a higher income, while only 17 percent had a lower income than in their former paid employment position.
Keywords: D22; J23; L26; M13; 330; entrepreneurship; self-employment; start-ups